STUDI POTENSI PLTS ATAP DI MAKASSAR UNTUK MENINGKATKAN PENGGUNAAN ENERGI TERBARUKAN DAN MENGURANGI EMISI KARBON - Octavia, Dea; Arvandhi Hutama; Divtara Tampoy; Rian Cahya Rohmana (Petro : Jurnal Ilmiah Teknik Perminyakan, 2023)
Indonesia is located below the equator and has high exposure to sunlight throughout the year, providing great potential for generating electrical energy from solar sources. The demand for electrical energy in Indonesia continues to increase every year, so that it is very important to take advantage of the abundant potential of solar energy to become a source of renewable energy for power generation. This study focuses on analyzing the potential and effectiveness of using solar power and the challenges in its use, especially in the Makassar area. Solar power can generate up to 112,000 GWp of electricity or the equivalent of 89,600,000 MW. One of the challenges faced in using solar panels is the high material and installation costs, as well as people's dependence on conventional electricity. The Indonesian government has set a target to obtain 23% of the total electricity capacity from renewable energy sources by 2025. One solution is to use a rooftop solar system which can directly convert solar radiation into electrical energy. The energy generated from the Rooftop PLTS system can be stored in a battery that is controlled by a regulator and used at night. The use of on-grid PLTS or Rooftop PLTS can provide the advantage of saving PLN's electricity by 39.9% to 110.5%. It can be concluded that using energy from solar panels in a month can produce carbon gas emissions by 3.3% or carbon gas emissions are reduced by up to 96.7%.